Agronomic performance and yield stability of extra-early maturing maize hybrids in multiple environments in the Sahel - Konate, L.; Badu-Apraku, B.; Coulibaly, M.; Menkir, A.; Laouali, M.N.; Meseka, S.K.; Mengesha Abera, W. (Elsevier, 2023)
Frequent occurrence of drought, heat, low soil fertility and Striga infestation are the main stress factors reducing maize yield in the Sahel. Adoption of stable multiple stress tolerant maize cultivars in the region is crucial for achieving food security. However, selection of a stable high yielding cultivar is complicated by genotype × environment interaction (GEI) due to differential responses to growing conditions. Eleven extra-early maturing multiple-stress tolerant maize hybrids and two checks arranged in a randomized complete block design was evaluated across nine locations for two years in Mali and Niger. The objectives of this study were to identify (i) stable and high-yielding maize hybrids, and (ii) suitable test locations for selecting promising extraearly maize hybrids. GGE biplot was used for graphical analysis. Significant genotype, location and GEI effects were detected for grain yield and number of ears per plant. EEWQH-13 produced the highest grain yield (3860 kg ha􀀀 1) while EEYQH-1 had the poorest yield (2663 kg ha􀀀 1) with trial mean of 3395 kg ha􀀀 1 for all hybrids. GGE biplot explained 69.6 % of the total variation in grain yield among the hybrids. The polygon view identified EEWQH-13 as the best hybrid across six of the nine test locations. EEPVAH-58 was identified as the most stable high yielding hybrid across the nine test locations followed by EEWQH-16 and EEWQH-13. The nine locations were clustered under two mega-environments (ME1, ME2). Among the nine test locations, Tara and Aderaoua clustered in ME1 were the most suitable ones for selecting promising extra-early maize hybrids for wider adaptation. The three hybrids, EEPVAH-58, EEWQH-16, and EEWQH-13, identified in this study could be recommended for on-farm evaluation to confirm the consistency of their yield performance for possible release and commercialization in Mali and Niger.